Synergy Effects of the Indian Summer Monsoon and the Tibetan Plateau Heating on Summer Rainfall over North China - Siwen Zhao; Jie Zhang; Zhihong Lv (Advances in Meteorology)
An analysis based on July-August precipitation reveals that there is a tripole pattern of the precipitation distribution, that is, significantly increased rainfall over North China (NC) is related to the increased rainfall over the Indian subcontinent (IS) and the decreased rainfall over the southeastern Tibetan Plateau (TP) and vice versa, that corresponds to the Indian summer monsoon (ISM) and TP heating pattern, which are interactive. Therefore, it is necessary to investigate the effect of NC rainfall-related atmospheric circulation and the physical linkage with the two thermal forcings together. The linear baroclinic model (LBM) is applied to determine the dynamics of the process. The results show that an enhanced ISM is accompanied by reduced TP heating, favors convection and easterly anomaly over the IS, and produces a Gill-type Rossby wave that affects the vorticity over North Africa. Meanwhile, there is another Rossby wave originating in North Africa and moving eastward to the Pacific Ocean, which interferes with circulation at mid- to high-latitudes, i.e., it strengthens the cyclone over the Baikal region and stretches the western Pacific subtropical high (WPSH) northward to northeastern Asia, and results in abundant water vapor transported to NC. Furthermore, the strong convection over the IS excites the Kelvin waves over the equatorial region, which moves eastward and generates anticyclones over Philippines, consequently leading to the Pacific-Japan (PJ) pattern. The PJ pattern cooperates with the wave train at midlatitudes, resulting in abundant water vapor being transported to NC. The summer rainfall over NC is therefore modulated by synergistic effect of both the ISM and TP heating.